Snowpack Dynamics in Arizona's Aspen Forests - Timmer, Michael J. (Arizona-Nevada Academy of Science, 1980)
From the Proceedings of the 1980 Meetings of the Arizona Section - American Water Resources Assn. and the Hydrology Section - Arizona - Nevada Academy of Science - April 11-12, 1980, Las Vegas, Nevada